1995
DOI: 10.1016/s0969-2126(01)00151-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the specific interaction of lysine-containing proline-rich peptides with the N-terminal SH3 domain of c-Crk

Abstract: The c-Crk SH3 domain engages in an unusual lysine-specific interaction that is rarely seen in protein structures, and which appears to be a key determinant of its unique ability to bind the C3G peptides with high affinity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
268
0
6

Year Published

1996
1996
1998
1998

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 246 publications
(290 citation statements)
references
References 48 publications
16
268
0
6
Order By: Relevance
“…At the same time, binding of the (K?R)-mutant peptide to the Grb2SH3(N) domain was greatly increased. These results were con®rmed and explained by ultrastructural data, which showed that the lysine is tightly bound in a uniquely structured pocket largely formed by an SH3 region named the`RT-loop' (Wu et al, 1995).…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…At the same time, binding of the (K?R)-mutant peptide to the Grb2SH3(N) domain was greatly increased. These results were con®rmed and explained by ultrastructural data, which showed that the lysine is tightly bound in a uniquely structured pocket largely formed by an SH3 region named the`RT-loop' (Wu et al, 1995).…”
Section: Introductionmentioning
confidence: 74%
“…An alanine scan through this C3G-CB-1 peptide demonstrated that the residues P 284 , L 286 , P 287 and K 289 are particularly important for the binding a nity towards the CrkSH3(1) domain. The lysine residue was shown to contribute strongly to the almost unique SH3 binding speci®city of CB-1 Wu et al, 1995). Replacement of K 289 by an arginine reduces the a nity of the CB-1 peptide approximately eightfold (to 17.2 mM) and signi®cantly a ects the interactions observed in the crystallised peptide-SH3 complex (Wu et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations